ML and ML2 complex formation between Ca(ii) and d-glucose derivatives in aqueous solutions. Issue 4 (5th January 2017) - Kutus, Bence; Ozsvár, Dániel; Varga, Norbert; Pálinkó, István; Sipos, Pál
Abstract : Besides the well-known ML species, Ca(ii ) forms ML2 complexes with carbohydrates having at least one carboxylate group and conformational flexibility. Abstract : The complex formation equilibria between Ca 2+ ions and six carbohydrate derivatives related tod -glucose was quantitatively characterized by potentiometry, freezing point depression and polarimetry. Complexation could not be observed ford -glucose, while weak association was deduced ford -sorbitol andd -mannitol. Stronger complexes are formed withd -gluconate andd -heptagluconate due to the presence of the carboxylate group. In addition to the plausible 1 : 1 species, the 1 : 2 species can also be detected at higher ligand to metal ratios. The ML type complex is also formed withd -glucuronate andd -glucarate. The strong association ford -gluconate andd -heptagluconate was attested by freezing point depression measurements. Polarimetric results show that for these two ligands the specific rotation of the complexed and free anions is only slightly different. The stability of the 1 : 1 complexes follows the order: mannitol < sorbitol < glucuronate < heptagluconate ≈ gluconate < glucarate. The formation of the ML2 type species has been established for polyhydroxy ligands having at least one carboxylate group in addition to the conformational flexibility.